Discurso médico, saúde pública e estratégias políticas para “Uma questão palpitante do tempo actual” : a emergência da luta contra o cancro em Portugal (1904-1923) - Costa, Rui Manuel Pinto (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present article approaches the scientifi c and political context that where in the origin of the institutionalization of the fi ght against cancer in Portugal over the fi rst quarter of the 20th century. One stresses the emerging medical speech, the main medical theories, as well as the fi rst statistical studies that prompted doctors and politicians to coordenate the fi ght against cancer. Although there were moments of medical tension and political disinterest, the project was materialized in 1923, with the establishment of the Instituto Português Para o Estudo do Cancro.